2021
DOI: 10.1016/j.jbi.2021.103777
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping coronavirus disease 2019 during a global health pandemic: Lessons learned from the characterization of an early cohort

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, EHR phenotyping pose many challenges, which could lead to inaccurately extracting the treatment status of the patient. 50 For example, drug exposure extraction from clinical text relies on accurate identification of text expressions that are negated (e.g., “ he could not be on Coumadin because of history of GI bleed ”) or hypothetical (e.g., “ Zofran 4 mg PO once a day as needed for nausea ”). 14 This is another reason for interpreting the results of over‐the‐counter drugs with caution because they are primarily extracted from clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…However, EHR phenotyping pose many challenges, which could lead to inaccurately extracting the treatment status of the patient. 50 For example, drug exposure extraction from clinical text relies on accurate identification of text expressions that are negated (e.g., “ he could not be on Coumadin because of history of GI bleed ”) or hypothetical (e.g., “ Zofran 4 mg PO once a day as needed for nausea ”). 14 This is another reason for interpreting the results of over‐the‐counter drugs with caution because they are primarily extracted from clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable subphenotype characterization that reflects the geographical and healthcare settings from which they are ascertained is crucial 46 . To date, variability between Mexican states and TCIs regarding severity are rarely reported 47,48,49 , nor assessed for variability independently from age and gender.…”
Section: State and Types Of Clinical Institutionmentioning
confidence: 99%
“…The current infrastructure and complexity of EHR systems vary across hospitals, which limits the capability of using EHR data for research purposes [ 9 ]. Data quality and related issues have been studied in many contexts, and the findings can vary across different institutions and different research studies [ 9 , 25 , 26 , 27 , 28 ]. Many such issues are generated during the documentation process at the point of care [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lynch et al evaluated the performance of ICD-10 code U07.1 for identifying COVID-19 patients using a manual chart review as a gold standard, and they found that the performance was low [ 26 ]. Similarly, DeLozier et al found that using laboratory testing (sensitivity = 93%) only to define COVID-19 patients outperformed the use of ICD-10 code U07.1 (sensitivity = 46.4%), which can be improved when combining the output of both definitions of ICD-10 and laboratory testing to yield a sensitivity of 100% [ 27 ]. Lynch et al reported the use of ICD-10 codes either alone or supported with laboratory tests is not sufficient for surveillance and research [ 26 ], as ICD-10 codes do not appear to capture cases correctly [ 30 ].…”
Section: Introductionmentioning
confidence: 99%